At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
Y Intercept: (0,-1)
X Intercept: (3,0)
Step-by-step explanation:
Let's rearrange the original equation to be in y intercept form
2x-6y=6
-6y=-2x+6 (isolate y on the left side by subtracting both sides by -2)
6y=2x-6 (we can divide both sides by -1 to eliminate the negative signs)
y=2/6x-1
the y intercept is when x = 0, so we can insert that into the new equation we have
y=2/6(0)-1
y=-1
we can also use the new formiula to find the x intercept, the x intercept is when y = 0
y=2/6x-1
0=2/6x-1
-2/6x=-1 (isolate x by subtracting both sides by 2/6x)
2/6x=1 (divide both sides by -1 again to get rid of the negative signs)
2x=6 (multiply both sides to get rid of the 6 in the denominator)
x=3 (divide both sides by 2 to isolate x)
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.